(untitled) (Global Journal of Medical Research, 2016)
Copper (II) oxide nanoparticles (CuO-NPs) are widely used in industry, cosmetics and medicine. People have increasingly been exposed to these active materials. Several studies indicate that CuO-NPs could be taken up by different organs and cause toxicities. However, there is still a lack of data on the toxicological effects of CuO-NPs in neuronal system. In the present study, the toxic potentials of CuO-NPs were investigated in human SH-SY5Y neuroblastoma cells. After assessment of their cellular uptake potential, cytotoxicity by MTT and neutral red uptake (NRU) and genotoxicity by comet assay were evaluated. Enzyme-Linked Immune Sorbent Assays (ELISA) determination of malondialdehyde (MDA), 8-hydroxydeoxyguanosine (8-OHdG), protein carbonyl (PC), and glutathione (GSH) levels for oxidative damage, and Annexin V-FITC with propidium iodide (PI) for apoptosis were used. In conclusion, CuO-NPs were found to accumulate in the cells and induced significant cytotoxic and genotoxic, and oxidative and apoptotic effects. CuO-NPs are hypothesized to dangerously affect human health, especially neuronal system.